Janusz Józef Węc, Germany’s Position on the System Reform of the European Union in the 2002–2016, Wydawnictwo Peter Lang, Berlin 2018, ss. 288. - Dulak, Michał (Rocznik Integracji Europejskiej, 2021)
Recenzja